Assessment of SARS-CoV-2 Stability in human and environmental matrices, and potential hazards. Issue 1 (2nd January 2023) - Amahmid, Omar; El Guamri, Youssef; Rakibi, Youness; Ouizat, Saadia; Yazidi, Mohamed; Razoki, Bouchra; Kaid Rassou, Khadija; Touloun, Oulaid; Asmama, Souad; Bouhoum, Khadija; Belghyti, Driss
ABSTRACT: In the context of the ongoing pandemic of COVID-19, SARS-CoV-2 was detected in human excreta and environmental matrices. The occurrence of SARS-CoV-2 in environmental compartments raises questions on its fate and stability in these matrices and its potential to spread in the exposed communities. This review focused on the stability of the SARS-CoV-2 in human excreta, wastewater, soils, crops, and other environmental matrices, that may be reached through human excreta and sewage products spreading. Little is known about the persistence and survival of SARS-CoV-2 in the environment. Up to now sewage sludge, soil and crops are seldom investigated implying the convenience of considering future researches focusing on SARS-CoV-2 in soils receiving wastewater and sewage sludge, as well as on grown crops. Information regarding SARS-CoV-2 persistence in environmental media is crucial to establish and implement effective policies and measures for mitigating the transmission of COVID-19 and tackling eventual future outbreaks.